SISTEM INFORMASI MANAJEMEN KEUANGAN PAUDQU NURUL IZZAH MENGGUNAKAN METODE RAPID APLICCATION DEVELOPMENT (RAD) BERBASIS WEB - Tri Ramadan, Aditya; Gilang Saputra; Mohamad Fadil Adha; Wasis Haryono (Tech-E, 2025)
This study presents the design and development of a web-based Financial Management Information System (FMIS) for PAUDQU Nurul Izzah using the Rapid Application Development (RAD) methodology to replace error-prone and time-consuming manual processes. Through stakeholder interviews with administrators, accounting staff, and teachers, we identified essential functional requirements such as transaction entry, automated report generation, and role-based access controls and nonfunctional needs for performance, security, and user-friendliness. Based on these requirements, we created data models, user interface mockups, and workflow diagrams, then rapidly built and refined a prototype in successive iterations of demonstration and feedback until it satisfied predefined accuracy and usability criteria. Comprehensive testing including unit, integration, and user acceptance tests confirmed that the system reliably records financial transactions and generates income statements, balance sheets, and cash flow summaries without manual intervention. Initial evaluations show a 60 percent reduction in transaction processing time and a decrease in month-end reporting from days to hours, while built-in audit trails and access controls enhance accountability and data integrity. By delivering digital ledgers, real-time dashboards, and automated reporting, this RAD-driven FMIS not only streamlines financial workflows at PAUDQU Nurul Izzah but also establishes a scalable model for modernizing administrative operations in other early childhood education institutions.